Comparative Study of Opioid Free versus Opioid Anaesthesia in Patients Undergoing Laparoscopic Cholecystectomy - Shakya, Shailendra; Vaidya, Preeti; Paudel, Bibek (Journal of Nepalgunj Medical College, 2022)
Introduction: Opioids have been used as a part of balanced anaesthesia and have known side effects. Opioid Free Analgesia is an emerging technique, based on avoiding intraoperative opioids. Aims: To compare the effectiveness of opioid-free versus opioid based anaesthesia. Methods: This comparative study involved 100 patients undergoing elective laparoscopic cholecystectomy under general anaesthesia with American Society of Anaesthesiologists I or II physical status. Out of 100 patients, 50 received Fentanyl (Group A) while another 50 (Group B) received Ketamine and Lignocaine. Parameters measured and compared were the gender, age, weight, ASA physical status, hemodynamic stability, postoperative pain intensity (VAS) and opioid requirements, as well as side effects. Results: Both groups were comparable with regards to age, gender, weight, American Society of Anaesthesiologists I or II physical status, mean duration of surgery. There was no significant difference between groups hemodynamics at all assessed times (p>0.05) intraoperatively. Visual Analogue Scale pain score in the first 24 hours postoperatively showed that patients in Group A, at all analyzed time points had higher Visual Analogue Scale scores than Group B, but statistically significant difference was confirmed during the first hour (p = 0.001). Seven(14%) in Group A and 5(10%) patients in Group B got intravenous tramadol only once while 5(10%) patients in Group A required twice, which was statistically significant (p=0.05). Intraoperatively, 2 patients (4%) in group A had bradycardia while none in group B, which was statistically insignificant (p=0.153). Postoperatively, nausea was more in group A than Group B i.e. 8% vs 4% (p=0.4). Conclusion: Opioid Free anaesthesia has a better benefit over Opioid anaesthesia with regard to postoperative pain score, opioid consumption and its side effects.